Application of foreign experience of development of project and innovative management at the defense enterprises (Journal of Economic Research & Business Administration, 2019)
This article is devoted to the study of the possibilities for the application of foreign experiencein the development of project and innovation management at the enterprises of the defense industryof the Republic of Kazakhstan (DI RK). For this purpose, a study was conducted on the experience ofimplementing project activities in various countries and identifying features. Given the fact that in thedevelopment of innovation and project management, some countries have advanced far ahead, it seemsuseful to study their experience in implementing effective management systems in the country’s defenseindustry enterprises. Military power and competitiveness are taken as a criterion to identify the countrieson which to focus for the study and application of their experience. The current state and developmenttrends of the defense industrial complex of other countries, as well as the experience of internationalcompanies in the implementation of innovation and project activities, have been studied. The study useddata from international organizations, country statistics, global indices and ratings. Among the scientificliterature studied the works of foreign and domestic authors on related topics. The study showed that theimplementation of project activities in different countries occurs at different speeds. As the experience ofother countries has shown, the increase in the amount of funding, in itself, does not ensure the country’smilitary competitiveness. The development of the military sector depends on many factors, in addition tothe amount of funding, among which innovativeness of projects, people’s competence, development ofmanagement systems and others are especially important. The practical significance of this work lies inthe fact that the findings and proposed recommendations can be useful in the recently initiated processesof introducing innovative and project management in the Ministry of Defense and Aerospace Industry,in general, and in defense enterprises, in particular.